Comparative Study of Fuelwood Consumption by Semi-Nomadic Pastoral Community and Adjacent Villagers around Corbett Tiger Reserve, India - Hussain, Aatif; Negi, A. K.; Singh, Rahul Kumar; Aziem, Showket; Iqbal, Kaiser; Pala, Nazir A. (Indian Forester, 2016)
The present study was carried out to understand the fuelwood resource use pattern by semi-nomadic pastoralist community (Van Gujjar) and adjacent villagers in and around Corbett Tiger Reserve, Uttarakhand, India. A total of nineteen settlements of Van Gujjars and fourteen adjacent villages were surveyed. Overall average fuelwood consumption of Van Gujjars community was found higher than adjacent villagers. But the average per capita fuelwood consumption of adjacent villagers was found higher than Van Gujjars. The fuelwood consumption by both communities was 1584.1 t dm and the observed total deforested wood was found 833.73 m3, which leads to the emission of various green house gasses. Inaccessibility of the area, lack of communication, high prices and a limited supply of alternative source of energy are largely responsible for the total dependence on nearby forests for fuelwood, fodder and other life supporting demands.